The Demise of Industrialism and What It Means to Business Education - Jung , Bohdan (Kwartalnik Nauk o Przedsiębiorstwie, 2011)
In the global economy work based on the creativity of the people becomes increasingly important. Thereby the conditions under which it is carried out are changing. The current model of employment shaped in the industrial age, when employees could work only in a certain place and time, does not responds more to new challenges. As a result, not only changes the style of work, but also the lifestyle of people employed in the sectors of the creative economy. Analyzing the nature of these changes the author wonders what, in turn, should be changed in the education system, in order to enable proper preparation of graduates to exercise this type of work.